REKAYASA NILAI PEMBANGUNAN GEDUNG SERBA GUNA UNIVERSITAS NEGERI SEMARANG - Jatmiko, Jatmiko; Wibowo, Ary; Sriyana, Sriyana; Dwi H., Jati Utomo (Jurnal Karya Teknik Sipil, 2013)
Value engineering of multipurpose building project Semarang State University conducted for optimization of cost and functionality. Value engineering is used to evaluate the project plan in order to save the budget costs, optimize performance and efficiency of time but still consider the quality of the work. Application of value engineering aims to obtain high-cost work items, bring alternative design ideas to replace the original design on selected work items and calculate the cost savings from the application of value engineering. Stages of this value engineering plans that include; stages of information, creative stage, analysis stage and the stage of recommendations. Identification of high-cost items of work with cost breakdown model and Pareto charts. Potential work item function analysis is performed to classify the basic functions and secondary functions in order to obtain the ratio of cost / worth, then performed a zero-one matrix analysis to determine the best alternative of testing against several criteria functions presented. Value engineering analysis results indicate that cost savings, for items slab occurred saving the value / cost of Rp. 3.274.245.393, 35 or 51.20 % of the initial cost of Rp. 6,394,649,122.60 and 8.57 % of the total project cost. For items foundations occurred saving the value / cost of Rp. 318,946,000 or 41.27 % of the initial cost of Rp. 772,790,000.00 and 1.19 % of the total project cost. For the cost of the item walls Eco Lite Panel larger Rp. 140,847,906.93 of the cost of masonry, but in terms of execution time Eco Lite Panels faster than bricks with the result of the acceleration time fee of Rp. 224.734.555,16 or 21,82 % of the cost of the wall work and 0.59 % of the total project cost. Physical Eco Lite Panel calsiboard coated on both sides to make more smooth and flat surface so that the surface can be directly painted. So the total cost savings after the engineering value is equal Rp. 3.817.926.101,65 or by 9.99 % of the total cost of the overall work of Rp. 38,199,420,000.00.